2013
DOI: 10.1080/03601234.2013.742386
|View full text |Cite
|
Sign up to set email alerts
|

Increased virulence of transgenicTrichoderma koningistrains to the Asian corn borer larvae by overexpressing heterologouschit42gene with chitin-binding domains

Abstract: The chit42 gene cloned from Metarhizium anisopliae lacks chitin-binding domain (chBD), which plays important roles in binding insoluble chitin. Five kinds of hybrid chitinase Trichoderma transformants were constructed in this study, where the chit42 gene was fused to chBDs derived from plant, bacterial, and insect sources. The transformant Mc4 harboring chBDs from bitter melon (Momordica charantia) displayed the highest chitinase activity among all chBDs. The chitinase activities of Mc4, chit42 Trichoderma tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The Trichoderma transformants harboring the hybrid chitinase gene overexpression cassette were selected and labeled as T. koningii Mc4. T. koningii Mc4 had been proven to have an enhanced insecticidal activity against the Asian corn borer larvae and antifungal capability toward Fusarium verticillioides and Rhizoctonia solani [2].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Trichoderma transformants harboring the hybrid chitinase gene overexpression cassette were selected and labeled as T. koningii Mc4. T. koningii Mc4 had been proven to have an enhanced insecticidal activity against the Asian corn borer larvae and antifungal capability toward Fusarium verticillioides and Rhizoctonia solani [2].…”
Section: Methodsmentioning
confidence: 99%
“…The species remains the most significant economic insect pest for corn. Our previous study revealed that an overexpression of the Metarhizium anisopliae chit42 gene with a chitin-binding domain (chBD) in Trichoderma koningii increases the biocontrol activity, particularly the virulence against the Asian corn borer larvae [2]. Transgenic Trichoderma could also hinder the growth and development of the larvae.…”
Section: Introductionmentioning
confidence: 99%
“…Extreme acting laccases were observed to be responsible for bioremediation activity in Pestalotiopsis palmarum when wheat bran was present and lignin peroxidases were produced when extra heavy crude oil was the only carbon and energy source [48,49]. Other enzymes such as chitinases produced by a psychrophilic fungus, Lecanicillium muscarium, could be applied for enhancing the activity of insecticides owing to their ability for acting on insect chitin exoskeleton [50,51]. Not only can the extremophilic fungi be used in bioremediation studies, but their isolation from extreme environments such as a deep biosphere habitat represented by fumarolic ice caves on Antartica's Mt.…”
Section: Extremophilic Fungimentioning
confidence: 99%
“…All the bacterial strains were cultured in Luria-Bertani (LB) medium at 37 °C and 220 rpm. Fungal phytopathogenic strains used in this study were collected by Shanghai Jiaotong University, Institute of Agricultural Environmental Microbial Engineering, including B. cinerea (Accession number:MN420829), M. oryzae (Accession number: GCA_002368485.1), F. graminearum (Accession number: MN396567), F. verticillioides [ 31 ], Rhizoctonia solani (Accession number: MN422011), Bipolaris maydis [ 32 ], Metarhizium anisopliae [ 33 ], and Curvularia lunata (Accession number: GCA_000743335.1) were routinely grown on potato dextrose agar (PDA) plate at 28 ℃.…”
Section: Methodsmentioning
confidence: 99%